Common Preemergence Herbicide Application Equipment and Considerations for Container Nursery Operations - Yuvraj Khamare; Chris Marble (EDIS, 2025)
Weeds are a costly and continual threat to ornamental nursery profitability. Due to a lack of labeled postemergence herbicide options, growers typically rely on timely preemergence herbicide applications for weed control, among other methods such as hand-weeding. While preemergence herbicides are usually the most cost-effective method of weed control, labor and chemical costs can still be high. In some cases, costs can be reduced and weed control can be improved by making changes to the equipment that is used to apply preemergence herbicides, or by potentially changing the herbicide formulation that is used. This publication was written for nursery managers to provide an overview of the types of herbicide equipment that are commonly used in nursery production, to discuss the advantages and disadvantages of each, and to highlight considerations regarding herbicide formulations and how they may impact different aspects of weed control and ornamental plant tolerance.